The Influence of Liquidity Ratio, Leverage, Activity Ratio and Profitability on Stock Prices : Empirical Study on Consumer Goods Industry Subsector Companies Listed on the Indonesia Stock Exchange for the Period 2017-2022 - Dede Rahmat; Suripto Moh. Zulkifli; Rinaldi Sri Herlambang (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Investment is a tool to earn income in the future. With so much uncertainty in generating income, it encourages someone to do something that will benefit themselves in the future. So that those who invest in the right way will feel calm about facing the lives of themselves and their families in the future. For investors, this research involved 54 companies and 11 companies were selected as samples through purposive sampling. The data analysis tools used in this research are classical assumption testing, multiple linear regression analysis, correlation analysis, coefficient of determination analysis, and hypothesis testing. The results of this research indicate that partially the Liquidity, Activity Ratio and Profitability variables have a significant effect on share prices. Leverage has no significant effect on stock prices. Simultaneously, the ratio variables Liquidity, Leverage, Activity and Profitability have a significant influence on Share Prices of 88.2% and the remaining 11.8% is influenced by other variables.